Perkembangan Beberapa Penyakit Daun Jagung Disebabkan Oleh Jamur Di Kecamatan Indralaya Utara Kabupaten Ogan Ilir - Hamidson, Harman; Suwandi, Suwandi; Effendy, TA. (Seminar Nasional Lahan Suboptimal, 2019)
Hamidson H, Suwandi S, Effendy TA. 2019. Development of some corn leaf diseases caused by mushrooms in  north Indralaya Sub-District Ogan Ilir District. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang  4-5 September 2019. pp. 528-534.  Palembang: Unsri Press. There have not been many reported of losses from corn disease. These diseases fluctuate from one place to another and from time to time, including leaf rust, Helminthosporium leaf blight, stem rot, cob rot by Diplodia, Ustilago, Aspergillus, etc., and viral diseases and fungi as well as. nematode root rot. This research was conducted to find types of diseases that attack the leaves of corn caused by fungi during generative phase. Information would include type and level of the disease. Plant samples were taken randomly for 50 mounds of mounds and observations were made with vulnerable time for seven days. The incidence of diseases found in the generative phase of corn plants were leaf rust (Puccinia polysora) and leaf blight (Bipolaris maydis Synonym Helminthosporium maydisY. Nisik. & C. Miyake). The percentage of incidence of the disease indicates that leaf rust disease in each village follows the include Tj. Pring, Tj. Senai, and Tj. Birds which were abouth: 83.15%; 80.42%; and 79.90%. Leaf disease in each village as follows: village Tj. Pring, Tj. Senai, and Tj. Bird: 52.02%; 86.79%; and 88.78%. The severity of the disease showed that leaf rust disease in each village as follows the village of Tj. Pring, Tj. Senai, and Tj. Birds: 50.98%; 47.22%; and 49.37%. Leaf disease in each village were as follows: village Tj. Pring, Tj. Senai, and Tj. Bird: 52.02%; 55.12%; and 55.30%. The incidence and severity of the disease indicate differences in disease progression in each village.Keywords: puccinia polysora, bipolaris maydis synonym helminthosporium maydis, corn